2020
DOI: 10.3389/fimmu.2020.591255
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dysbiosis and Autoimmunity: From Local Periodontal Responses to an Imbalanced Systemic Immunity. A Review

Abstract: The current paradigm of onset and progression of periodontitis includes oral dysbiosis directed by inflammophilic bacteria, leading to altered resolution of inflammation and lack of regulation of the inflammatory responses. In the construction of explanatory models of the etiopathogenesis of periodontal disease, autoimmune mechanisms were among the first to be explored and historically, for more than five decades, they have been described in an isolated manner as part of the tissue damage process observed in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 237 publications
(298 reference statements)
1
40
0
3
Order By: Relevance
“…The role of the human microbiota in autoimmune diseases has attracted increased attention ( 24 ). However, how the oral microbiota affects PBC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the human microbiota in autoimmune diseases has attracted increased attention ( 24 ). However, how the oral microbiota affects PBC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown an association between IL17 and many inflammatory and autoimmune diseases such as systemic lupus erythematosus, sclerosis multiple, asthma and inflammatory bowel disease (IBD) ( 112 ). Alternatively, tolerogenic DCs can eliminate or block T cells, resulting in resolution of ongoing immune responses and prevention of autoimmune responses, which despite having been reported as widely prevalent in oral mucosa, seem to be related to non-pathologic responses and even represent non-recognized physiological functions as the immune removal of debris ( 115 , 116 ). Alternatively, tolerogenic DCs can eliminate or block T cells, resulting in resolution of ongoing immune responses and prevention of autoimmunity ( 115 ).…”
Section: Epithelia/malt Interactions and The Fate Of The Immune Response In The Underlying Lamina Propriamentioning
confidence: 99%
“…Besides genetics, epigenetic modifications as a result of the interaction of bacterial metabolites and epigenetic enzymatic reactions, are also involved in pathogenesis of both PD and SLE [ 48 ]. Epigenetic mechanisms, such as DNA methylation and histone modification can trigger breakdown of immunological homeostasis of periodontal environment, but further investigations are needed to a more complete understanding of cyclic inflammation/dysbiosis process.…”
Section: Biological Basics For a Potential Relationship Between Pd And Slementioning
confidence: 99%
“…Potential mechanisms linking the SLE with the pathogenesis of PD include (i) the effects of systemic immune dysregulation on subgingival microbiota; (ii) the SLE-induced imbalance between pro-inflammatory and anti-inflammatory cytokines, which seems to be the cause of tissue damage [ 36 ]; (iii) the activation of autoreactive B cells and dysregulation of several other immune cell types, including macrophages, neutrophils, CD4+ T cells, and dendritic cells [ 48 ].…”
Section: Biological Basics For a Potential Relationship Between Pd And Slementioning
confidence: 99%